(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study examines the electronic marriage contract from both Islamic jurisprudential and legal perspectives, considering it a modern form that has emerged due to the increasing reliance on digital technologies for documenting official transactions. Given that marriage is among the most sacred contracts in Islamic law, with profound implications for family structure and societal stability, its transition to an electronic environment raises essential questions regarding its legitimacy, validity, its unique nature, and compliance with both Sharia and statutory regulations. The research aims to identify the unique characteristics of electronic marriage contracts and assess the fulfillment of their fundamental elements and conditions, including the presence of a guardian (wali), witnesses, the exchange of offer and acceptance (ijab and qabul), the dowry (mahr), and other legal prerequisites. It further explores associated legal and technical challenges, such as identity fraud, data manipulation, and the lack of formal Sharia-based documentation. Employing an analytical methodology grounded in Islamic jurisprudence and contemporary legal concepts, the study proposes a comprehensive model for electronic marriage contracts that balances Sharia requirements with technical safeguards. The paper concludes with a set of legal and technical recommendations aimed at regulating and facilitating the secure and reliable adoption of such contracts.